2022
DOI: 10.1590/2177-9465-ean-2021-0467pt
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida relacionada à saúde de profissionais de enfermagem na Bahia na pandemia da COVID-19

Abstract: RESUMO Objetivo Identificar fatores associados à qualidade de vida relacionada à saúde de profissionais de enfermagem da Bahia durante a pandemia da COVID-19. Método Estudo transversal, amostragem tipo snowball com 113 enfermeiras(os) e técnicas(os) de enfermagem. De setembro/2020 a maio/2021, num formulário eletrônico, coletaram-se informações sociodemográficas, ocupacionais, epidemiológicas e de qualidade de vida, avaliada pelo questionário WHOQOL-BREF nos seus domínios Físico, Psicológico, Relações sociai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 21 publications
1
9
0
7
Order By: Relevance
“…Family and friends had a greater positive impact than ‘significant others’, which is consistent with the findings of other researchers 20 , 21 , 31 , 48 and indicates the potential of these networks as a source of social support for CHWs. Thus, strategies favoring and expanding social support should be implemented, among other things, by creating space for the exchange of experiences, improving working conditions, implementing occupational health actions through psychosocial support programs, and strengthening collaboration and teamwork skills 49 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Family and friends had a greater positive impact than ‘significant others’, which is consistent with the findings of other researchers 20 , 21 , 31 , 48 and indicates the potential of these networks as a source of social support for CHWs. Thus, strategies favoring and expanding social support should be implemented, among other things, by creating space for the exchange of experiences, improving working conditions, implementing occupational health actions through psychosocial support programs, and strengthening collaboration and teamwork skills 49 .…”
Section: Discussionsupporting
confidence: 90%
“…The availability of social support for health workers in terms of instrumental and emotional factors and social interaction has been shown to preserve QoL in both the occupational setting and the family setting 17 19 , which has become increasingly evident during recent pandemics 20 , 21 . Studies published before the pandemic identified sex, age, schooling, workplace, family income, smoking, psychological aspects and satisfaction as determinants of QoL 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Before the pandemic, this variable was already related to QoL in all domains, indicating that younger people tend to have less impaired QoL, which is also associated with better WA. Younger professionals have less occurrence of chronic pain, need for medical treatment and are more willing to carry out daily activities ( 35 , 36 , 37 ) .…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, the general population’s QoL was affected, with a drastic impact on the social component, due to recommended social distancing, which required adaptations and greater support from technology in maintaining bonds and connections with family and friends, with social support being a significant factor for the adequate QoL of healthcare professionals ( 20 , 38 ) . However, the low QoL found in the present study reinforces that nursing professionals, even before the pandemic, already showed regular or poor perception in the QoL physical, psychological and environmental domains, in addition to changes in WA, sleep and rest, fatigue and cognitive aspects, factors statistically associated with work overload, lack of human and material resources, inadequate physical structure, stress, low wages, disorganized environment, poor interpersonal relationships with colleagues, patients and managers, lack of social support, lack of physical activity and leisure, irregular sleep and lack of safety ( 31 , 35 , 37 , 39 , 40 , 41 ) .…”
Section: Discussionmentioning
confidence: 99%
“…. Furthermore, its presence determines a change in body image, which requires personal transformations that can generate stress when demands arise that overload or exceed an individual's adaptive capabilities (Miranda et al, 2018;Ferreira et al, 2021). Furthermore, as observed by Ferreira et al (2017), the stoma patient begins to face physical, emotional and psychosocial issues that profoundly interfere with their daily lives.…”
Section: Category 1 Daily Life Of People With An Intestinal Stomamentioning
confidence: 99%